National study on the adequacy of antidotes stocking in Lebanese hospitals providing emergency care. Issue 1 (December 2016) - Mansour, Anthony; Al-Bizri, Layla; El-Maamary, Jad; al-Helou, Amanda; Hamade, Rayan; Saliba, Elie; Khammash, Dina; Makhoul, Karim; Matli, Kamal; Ghosn, Nada; Deeb, Mary; Faour, Wissam
Abstract Background Antidotes stocking is a critical component of hospital care for poisoned patients in emergency. Antidote stocking represents a major health challenge worldwide and in Lebanon. Systematic data monitoring of antidote stocking in Lebanese hospitals is lacking. The objective of this study is to assess the adequacy of antidotes stocking in Lebanese hospitals according to type and quantity and explore the characteristics associated with their differential availability. Methods Data collection to assess antidote availability and its correlate was undertaken through a self-administered questionnaire. The questionnaires were distributed by the unit of surveillance at the Ministry of Public Health to eligible hospitals providing emergency care services. The list of essential antidotes was adapted from the World Health Organization (WHO) list and the British Columbia Drug and Poison Information Centre. Results Among the 85 Lebanese hospitals surveyed none had in stock all the 35 essential antidotes required. The frequency of stocking by type of antidote varied from a minimum of 1.2 % of the hospitals having a (cyanide kit) to 100 % availability of (atropine and calcium gluconate). Teaching hospitals and those with a large bed-capacity reported a higher number of available antidotes for both immediate and non-immediate use than non-teaching hospitals while controlling for the hospital geographical region and public vs private sector. Conclusion The Lebanese hospitals have a suboptimal stock of essential antidotes supply. It is recommended that the Lebanese Ministry of Public Health monitors closely on the hospital premises the adequacy and availability of essential antidotes stock.